2016
DOI: 10.1242/jcs.196337
|View full text |Cite
|
Sign up to set email alerts
|

Xpf suppresses the mutagenic consequences of phagocytosis in Dictyostelium

Abstract: As time passes, mutations accumulate in the genomes of all living organisms. These changes promote genetic diversity, but also precipitate ageing and the initiation of cancer. Food is a common source of mutagens, but little is known about how nutritional factors cause lasting genetic changes in the consuming organism. Here, we describe an unusual genetic interaction between DNA repair in the unicellular amoeba Dictyostelium discoideum and its natural bacterial food source. We found that Dictyostelium deficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…This lack of a defect might be a consequence of redundant killing mechanisms or of challenge with a bacterium that is easily killed. Intriguingly, a D. discoideum mutant lacking the Xpf nuclease, a component of DNA damage repair machinery, accumulates more mutations when grown on a range of bacteria including Klebsiella than when grown axenically in media ( 181 ). One possible explanation is that Xpf is required to repair DNA damaged by ROS generated in response to bacteria.…”
Section: Microbicidal Phagosomementioning
confidence: 99%
“…This lack of a defect might be a consequence of redundant killing mechanisms or of challenge with a bacterium that is easily killed. Intriguingly, a D. discoideum mutant lacking the Xpf nuclease, a component of DNA damage repair machinery, accumulates more mutations when grown on a range of bacteria including Klebsiella than when grown axenically in media ( 181 ). One possible explanation is that Xpf is required to repair DNA damaged by ROS generated in response to bacteria.…”
Section: Microbicidal Phagosomementioning
confidence: 99%
“…The role of ROS production in bacterial growth and killing has been unclear [ 54 ]. However, these data suggest the ability of D. discoideum cells to withstand oxidative stress is crucial for normal growth [ 55 ]. It is also interesting to note the enrichment of terms associated with lipid composition, including genes associated with sphingolipid metabolism.…”
Section: Resultsmentioning
confidence: 99%
“…Defects in FANCD2 leads to a failure of the radiation-induced block of DNA replication and to sensitivity to DNA damaging agents (Zhang et al, 2009). In addition, the Dictyostelium amoebae use the DNA repair nuclease Xpf, an endonuclease associated to the FA complex, to protect their genome from mutagens released during the consumption of bacteria (Pontel et al, 2016).…”
Section: Dictyostelium Life Cyclementioning
confidence: 99%
“…cisplatin), the FA component Xpf/ERCC4 has been shown to be crucial during the vegetative stage of life (Zhang et al, 2009). Xpf deficient cells display normal growth rate when cultured on axenic medium but a severe growth defect is observed when cells are fed on bacteria (Pontel et al, 2016). A deeper characterization of the mutant indicated that bacterial consumption leads to mutagenic events.…”
Section: Ancient Organism New Avenuesmentioning
confidence: 99%